2018
DOI: 10.1097/mat.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Systemic Heparin Versus Bivalirudin in Adult Patients Supported by Extracorporeal Membrane Oxygenation

Abstract: Systemic anticoagulation is a standard of care in adult patients supported by extracorporeal membrane oxygenation (ECMO) to prevent circuit thrombosis and subsequent thromboembolic events. Unfractionated heparin has long been considered the anticoagulant of choice, but emerging evidence reports successful ECMO runs with direct thrombin inhibitors. This retrospective study sought to determine whether bivalirudin offers distinct clinical benefits as the anticoagulant of choice in ECMO. Primary end points include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(158 citation statements)
references
References 22 publications
6
148
2
1
Order By: Relevance
“…Many institutions use heparin as their primary anticoagulant, but recently some institutions have started using bivalirudin instead of heparin. 69 While heparin requires binding to antithrombin and heparin cofactor II for anticoagulant action, bivalirudin has a direct effect, does not need to bind to other proteins to show anti-thrombin action, and, therefore, has a more stable effect. 70,71 In addition, release of tissue factor pathway inhibitor by heparin is another significant contributor to anti-Xa action.…”
Section: Extracorporeal Membrane Oxygenation and Hemostatic Disturbancesmentioning
confidence: 99%
“…Many institutions use heparin as their primary anticoagulant, but recently some institutions have started using bivalirudin instead of heparin. 69 While heparin requires binding to antithrombin and heparin cofactor II for anticoagulant action, bivalirudin has a direct effect, does not need to bind to other proteins to show anti-thrombin action, and, therefore, has a more stable effect. 70,71 In addition, release of tissue factor pathway inhibitor by heparin is another significant contributor to anti-Xa action.…”
Section: Extracorporeal Membrane Oxygenation and Hemostatic Disturbancesmentioning
confidence: 99%
“…Bohman et al 5 showed similar thrombotic event rates and blood loss between heparin and bivalirudin. Berei et al 6 depicted similar rates of thrombotic events between the two agents and no differences were observed in percent time activated partial thromboplastin time (aPTT) within the therapeutic range, neurological events, vascular complications, or major and minor bleeding incidents. Given the limited evidence on the efficacy and safety profiles of UFH compared with bivalirudin, this retrospective study aims to analyze the rates of composite thrombotic complications, major bleeding, and mortality events in patients who were supported by ECMO and received heparin‐ or bivalirudin‐based anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Bohman et al 5 showed similar thrombotic event rates and blood loss between heparin and bivalirudin. Berei et al 6 depicted similar rates of thrombotic events between the two agents and no differences were observed in percent time activated partial thromboplastin time (aPTT) within the therapeutic range, neurological events, vascular complications, or major and minor bleeding incidents.…”
Section: Introductionmentioning
confidence: 99%
“…Heparin pharmacokinetics and pharmacodynamics are highly variable as it binds proteins and cells relatively indiscriminately, as it is eliminated through various mechanisms (including endothelial and macrophage metabolism) and as it exerts its effect through antithrombin III, which can often become deficient in patients on ECLS. 58 The parameter to use for monitoring and its target are still uncertain. 50 Common parameters for titrating anticoagulation include activated clotting time (ACT) or activated partial thromboplastin time (aPTT).…”
Section: Patient Management During Vv-ecls Hemostasismentioning
confidence: 99%